Analisis Yuridis Pembentukan dan Sinergitas Korps Pemberantasan Tindak Pidana Korupsi (Kortas Tipikor) Polri dalam Upaya Pemberantasan Korupsi di Indonesia - Sipayung, Baren (Indonesian Journal of Law and Justice, 2024)
Corruption is an extraordinary crime deeply rooted in Indonesia's social and political structures. Combating corruption is a critical agenda requiring adaptive and synergistic strategies. One strategic step is the establishment of the Corruption Eradication Task Force (Kortas Tipikor) within the Indonesian National Police (Polri), aimed at optimizing anti-corruption efforts through synergy and coordination among law enforcement agencies. This research employs a qualitative approach using a normative-juridical method to examine the formation of Kortas Tipikor Polri, analyze its duties and functions, and assess its synergy with other institutions such as the Corruption Eradication Commission (KPK) and the Audit Board of Indonesia (BPK). The findings indicate that the formation of Kortas Tipikor Polri is a strategic step that can strengthen anti-corruption efforts. Additionally, the study identifies several challenges in establishing Kortas Tipikor, such as the potential overlap in case handling and the need for clear regulations regarding the division of duties and authority between Kortas Tipikor and other law enforcement agencies. The synergy between Kortas Tipikor Polri, KPK, BPK, and community involvement is key to achieving success in eradicating corruption.